OPTIMISM AND PHYSICAL ACTIVITY PERCEPTION IN URBAN PARK USERS OF MONTEVIDEOOPTIMISM AND PHYSICAL ACTIVITY PERCEPTION IN URBAN PARK USERS OF MONTEVIDEO - Tutte Vallarino, Verónica (2011)
This paper focuses on the study of the pessimistic-optimistic profiles in users of a community park, and the perception of their own physical activity. One of our major interests is to compare and further the understanding of these variables, as well as to analyze how they relate to gender. Pessimistic-optimistic profiles were evaluated using the Life Orientation Test (LOT-R) developed by Scheier and Carver (1985), and its Spanish version by Otero-López, Luengo, Romero, Triñanes, Gómez and Castro (1998), while perception of physical activity was evaluated by a single question with a dichotomous response. 45 park users, between 17 and 53 years old, took part in this study. The results show a statistically significant bias in the optimism-pessimism factor; with the optimistic profile representing 82% of the sample. We did not find any statistically significant gender related bias in the optimism- pessimism factor. We have found a statistically significant gender related bias in the perception of own physical activity in relation to gender, with men showing higher scores. Finally, the result allows us to establish that there is a predominance of optimistic people who see themselves as active persons. However no statistically significant differences were observed when optimism and active self perception, or pessimism and passive self perception, were analyzed.